I wonder why whales sing and other questions about sea life - Harris, Caroline (London Kingfisher Publ.)
Este libro muy bien ilustrado contiene preguntas varias acerca de la vida animal marina con sus respectivas respuestas elaboradas de una manera muy sencilla .
Why do fish not drown?.-- Why do divers need headlights?.-- Where does grass grow under water?.-- Which animal swims by waving?.-- Why are octopuses like jet planes?.-- Why does a fish need fins?.-- Which fish uses a rod to catch food?.-- What uses combs for eating?.--What looks like a flower but is really trap?.-- Which crab borrows its house?.-- Which shellfish digs with its foot?.--Why do some fish have their eyes on their side?.-- Why are lionfish like porcupines?.-- Which fish wears armour?.-- What hides in ink?.-- Why do baby dolphins need guards?.-- What jumps up waterfalls?.-- What is busy at full moon?.-- Where can you see smoke?.-- What are sponges?.-- Which animals march in line?.-- Which is the brainiest part of the ocean?.-- What lettuce would make a nasty sandwich?.-- What has a funny home?.-- Why do whales sing?.-- What is psyhopping?.-- What causes strandings?.--How do dolphins stand up?.-- What is like an elephant?.-- How do seals and sealions keep warm?.-- How do sharks find their food?.-- What is strange about a shark's skeleton?.-- What use is a long tail?.-- How dangerous are sharks?.-- Which fish has binoculars?.-- What looks like the nigth sky?.-- When is a spider not a spider?.-- Which bird hangs its wings to dry?.-- Why do crabs run sideways?.-- Which lizard goes swimming?.-- What is whalewatching?.-- How can satellites help sea creatures?.-- Who cleans beaches?
Keywords: Inglés e n la literatura; Libros Ilustrados Para Ninos; Vida marina